(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article discusses innovative approaches to radio monitoring in Kyrgyzstan, focusing on the use of artificial intelligence and unmanned aerial vehicles. It presents a structural-functional diagram of the radio monitoring system, which includes distributed ground stations and mobile unmanned aerial vehicles for monitoring remote areas. The article outlines the main operational stages of the system and provides technical requirements and recommendations for effective functioning. Special attention is given to data transmission security, long-term storage, data analysis, and staff training. Examples of successful implementations of similar technologies in countries like South Korea and Germany are provided, with discussion on their adaptation for Kyrgyzstan. The conclusion emphasizes the importance of artificial intelligence and unmanned aerial vehicles in spectrum management and the sustainable development of the country’s telecommunications infrastructure.